Ekspresi CTR1 dan ATP7B sebagai Prediktor Respons Kemoterapi Neoadjuvan Cisplatin pada Kanker Serviks IIB - SUARTA, PUTU AGUS (Indonesian Journal of Cancer, 2015)
The locally advanced cervical cancer is common in Indonesia and with limitation of radiation, chemotherapy is used as a neoadjuvant treatment. However the clear mechanism of accumulation chemotherapy in cervical cancer is still unclear. The purpose this study to determine CTR1 and ATP7B expression as a predictor of response to neoadjuvant chemotherapy cisplatin in cervical cancer IIB The design of this research is observational analytic form prospectively on 30 sample cervical cancer stage IIB. Before chemotherapy, Cervical biopsy was taken to evaluate expression CTR1 and ATP7B and MRI was done to measure the tumor volume. Furthermore, four cycles neoadjuvat chemotherapy (NAC) cisplatin 50mg/m2 every weeks. Two - three weeks after complete chemotherapy, repeated MRI examination. Assessment response to chemotherapy was catagorized by RECIST. Results: 30 samples obtained from the study of cervical cancer, before chemotherapy the smallest volume 23.35 cm3 and the greatest 276.23 cm3. After chemotherapy smallest 2.14 cm3 and largest 422.11 cm3. Chemotherapy response obtained Partial Response (PR) 23 (76.7%), Stable Disease (SD) 5 (16.6%), Progressive Disease (PD) 2 (6.7%). Relationship CTR 1 expression and response to chemotherapy according to RECIST obtained p value 0.002. Relationship ATP7B expression and chemotherapy response according to RECIST obtained with p value 0.009. In multiple logistic regression analysis obtained CTR 1 with p 0.006 and p value 0.454 ATP7B. Conclusions: CTR1 and ATP7B expression can be used as a predictor of response to chemotherapy neoadjuvant cisplatin in cervical cancer IIB, CTR expression more better as a predictor of response to neoadjuvant chemotherapy.Keyword: Neoadjuvant chemotherapy, MRI, Cisplatin, RECIST, CTR1 ATP7BÂ ABSTRAKKanker serviks lokal lanjut masih menjadi masalah umum di Indonesia. Dengan keterbatasan radiasi maka kemoterapi sebagai neoadjuvan dipakai sebagai alternatif pengobatan. Mekanisme pasti akumulasi obat kemoterapi masih belum jelas. Penelitian ini bertujuan untuk mengetahui ekspresi CTR1 dan ATP7B sebagai prediktor respons terhadap kemoterapi cisplatin pada kanker serviks IIB. Rancangan penelitan ini adalah analitik observasional dengan bentuk prospektif. Dari 30 sampel penelitian kanker serviks IIB, dilakukan pemeriksaan MRI untuk mengukur volume serviks dan parametrium serta biopsi serviks untuk dilakukan pemeriksaan IHC (immunochemistry) CTR1 dan ATP7B. Selanjutnya diberikan Neoadjuvat chemotherapy (NAC) cisplatin 50 mg/m2 tiap minggu 4 kali. Setelah 2â3 minggu setelah NAC dilakukan pemeriksaan MRI ulangan. Penilaian respons kemoterapi dilakukan dengan RECIST. Hasil penelitian menunjukkan dari 30 sampel penelitian sebelum kemoterapi, volume serviks dan parametrium terkecil 23,35 cm3 dan terbesar 276,23 cm3. Setelah kemoterapi, terkecil 2,14 cm3 dan terbesar 422,11 cm3. Respons kemoterapi didapatkan Partial Response (PR) 23 (76.7%), Stable Disease (SD) 5 (16.6%), Progressive Disease (PD) 2 (6.7%). Hubungan ekspresi CTR 1 dan respons kemoterapi sesuai RECIST didapatkan dengan nilai p 0,002. Hubungan ekspresi ATP7B dan respons kemoterapi sesuai RECIST didapatkan dengan nilai p 0,009. Pada analisis regresi logistik ganda didapatkan CTR 1 dengan nilai p 0,006 dan ATP7B nilai p 0,454. Penelitian ini menyimpulkan bahwa ekspresi CTR1 dan ATP7B dapat dijadikan sebagai prediktor respons Neoadjuvant chemotherapy cisplatin pada kanker serviks IIB. Bila dibandingkan, ekspresi CTR 1 lebih baik sebagai prediktor respons kemoterapi neoadjuvant.Kata kunci: Neoadjuvant chemotherapy, MRI, cisplatin, RECIST, CTR1 ATP7B